Crystallization of poly(3‐hydroxybutyrate‐co‐3‐hydroxyhexanoate) during melt extrusion promoted by residual crystals. Issue 4 (3rd June 2019) - Aoyama, Taizo; Sato, Harumi; Ozaki, Yukihiro
Abstract: Poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyhexanoate) (PHBH) is a biodegradable and highly flexible polymer, which should have various applications like inflation film, T die extruded films and sheets, injection‐molded and blow‐molded articles, etc. Despite its attractive features, it suffers from the limitation of slow crystallization during molding, and none of the numerous nucleating agents examined to resolve this issue has yet proven successful. The addition of a higher‐melting biodegradable polyester is reported to be an effective solution, with the residual crystals preserved during PHBH melting being important for subsequent crystallization. However, this phenomenon is only observed under static conditions, for example, during differential scanning calorimetry and spectroscopic analysis using a variable temperature cell. In this study, the relationship between the amount of residual crystals and the subsequent crystal behavior was investigated under dynamic conditions, such as practical extrusion molding. Online near‐infrared spectroscopy was used to analyze the residual amount of crystals at the extruder outlet and explore the crystallization behavior of the extruded strands in real time. Even under the dynamic conditions, a close relationship was found between the amount of residual crystals and the subsequent crystallization behavior. In addition, the Avrami exponent ( n ) and the crystallization rate constant ( k ) were analyzed. Abstract : Although poly(3‐hydroxybutyrate‐ co ‐3‐hydroxyhexanoate) (PHBH) is highly flexible and biodegradable with wide application potential, its crystallization during molding is quite slow, which restricts its practical applications. The relationship between the residual crystal amount and subsequent crystallization was observed in real time by online near‐infrared and it was found that the residual crystal amount was very importance for subsequent crystallization of PHBH under dynamic conditions such as practical extrusion molding.